Knowledge and skill levels in violin music among the vocal music students of the university of jaffna - Darshanan, S.; Kayathiri, P. (university of Jaffna, 2014)
The students for the Bachelor of Fine Arts (Carnatic Vocal Music) students have been selected to the course based, on their advanced level (+2) Results for the subject Carnatic Vocal Music, and on their Z score and on the entrance practical examinations for Carnatic Vocal Music. But, during their nd rd th 2 , 3 , and 4 year studies inside the University of Jaffna, Department of Music, they have to choose their elective course units among the pool of Violin, Veena and Mruthangam. The results of the pilot study show that there are identical differences in the performing skills and knowledge in Violin Music, among the vocal music students who selected their choice as violin music. Therefore this nd study determined to find out the various knowledge and skill levels in violin music of the 2 year B.F.A. (Vocal Music) students. The hypothesis is set as “There are significant differences in the knowledge and skill levels in violin music among the vocal music students.” The research adopts the questionnaire survey method and through a statistical analysis on the grades which the students gained for violin music in the in course assessment results as they mentioned in the questionnaire, in order to find out the results. The analysis reports support the hypothesis. The conclusion would be there are three categories of students among the vocal music students who choose the violin music as their elective course unit and they are; already learnt violin in private classes and obtained certificates from the private exam boards, Already learnt violin privately but doesn't obtain the certificates, not learnt the violin music at all. The recommendation to the society would be, the different teaching strategies have to be introduced for the each three groups in order to improve their examination performance in future.
Keywords: Violin; Violin music; Violin education; University education; Violin educational strategies